2003
DOI: 10.1021/la034209c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Interaction between Surface-Bound Alkylamines and Gold Nanoparticles

Abstract: In addition to alkanethiols and phosphine derivatives, alkylamines have been investigated as capping agents in the synthesis of organically dispersible gold nanoparticles. However, reports pertaining to gold nanoparticle derivatization with alkylamines are relatively scarce and their interaction with the underlying gold support is poorly understood. In this paper, we attempt a more detailed examination of this problem and present results on the Fourier transform infrared spectroscopy, thermogravimetry, nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
313
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(341 citation statements)
references
References 45 publications
20
313
1
1
Order By: Relevance
“…Nanoparticles have incredible importance due to their unusual optical (Krolikowska et al, 2003), chemical (Kumar et al, 2003), photoelectrochemical (Chandrasekharan & Kamat, 2000) and electronic (Peto et al, 2002) properties. The optoelectronic and physicochemical properties of nanoparticles are strongly dependent on particle size (Alivisatos, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have incredible importance due to their unusual optical (Krolikowska et al, 2003), chemical (Kumar et al, 2003), photoelectrochemical (Chandrasekharan & Kamat, 2000) and electronic (Peto et al, 2002) properties. The optoelectronic and physicochemical properties of nanoparticles are strongly dependent on particle size (Alivisatos, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that amine binds strongly to AuNPs, 11,12 and therefore the exocyclic amines in melamine could play an important role in the melamine-AuNP interaction. To examine the specificity of colorimetric changes of the AuNPs, additional control molecules containing exocyclic amines were also mixed with AuNPs.…”
mentioning
confidence: 99%
“…At the beginning, the interaction mostly involves electrostatic interaction. Next, direct contact between gold nanoparticles and amine chains (in the case of multifunctional modifiers) results in the formation of strong gold-nitrogen coordination bonds [22][23][24]. Microscopic analysis (Fig.…”
Section: Deposition Of Gold Nanoparticlesmentioning
confidence: 99%